2017
DOI: 10.1111/1747-0080.12346
|View full text |Cite
|
Sign up to set email alerts
|

Successful long‐term maintenance following Nutrition Care Process Terminology implementation across a state‐wide health‐care system

Abstract: Immediate improvements following the NCPT implementation project were sustained over three years. Moving forward, a professional focus on continuing to incorporate NCPT into standard practice will provide structure for process and outcomes assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 13 publications
4
20
0
3
Order By: Relevance
“…In Sweden, however, the implementation process started quite early, and knowledge about the NCP is widespread; thus, this result remains to be explained (30) . Earlier research regarding NCP, as well as other innovations, has identified support from workplace and management as being important requirements for successful implementation (18,19,23,27,(36)(37)(38)(39)(40) . Swedish and US studies have described professional isolation, with lack of support and understanding from management and workplace, especially in those who worked as the only dietitian in a multiprofessional environment and in rural areas (19,41) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden, however, the implementation process started quite early, and knowledge about the NCP is widespread; thus, this result remains to be explained (30) . Earlier research regarding NCP, as well as other innovations, has identified support from workplace and management as being important requirements for successful implementation (18,19,23,27,(36)(37)(38)(39)(40) . Swedish and US studies have described professional isolation, with lack of support and understanding from management and workplace, especially in those who worked as the only dietitian in a multiprofessional environment and in rural areas (19,41) .…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising because the Nordic countries are often highlighted as early adopters of health information technology . The use of electronic health records has earlier been suggested as an important enabler in NCP implementation, although, because the Nordic countries still all have a rather low implementation level, other aspects might be more important .…”
Section: Discussionmentioning
confidence: 99%
“…Para estudiar la implementación y expansión internacional del PAN y los factores que la favorecen o limitan se han realizado diferentes trabajos. Entre ellos, el Proyecto INIS (International NCP/NCPT Implementation Survey), la mayor encuesta actualmente publicada, pone de manifiesto una tendencia creciente en el uso de los recursos relacionados con el PAN y la TE y la colaboración internacional en la investigación nutricional 9,10,25,28,49,50,[61][62][63] .…”
Section: Implementación Y Evaluación Del Proceso De Atención Nutriciounclassified
“…For dietitians, this includes culturally appropriate, safe, ethical and effective practice, improving nutritional health, using and generating new evidence and effectively working with others to achieve our end users’ goals . Arguably, the Nutrition Care Process Terminology framework provides a structure in which to focus on quality, safe and effective nutrition outcomes for individuals and communities, which has been found to be accepted by the profession . The National Competency Standards for Dietitians in Australia provide the framework for workforce development and the Accreditation Standards provide scope with which to guide the preparation of the workforce.…”
mentioning
confidence: 99%